「해양경찰법」 제정에 관한 연구: 해양경찰청장 임명 관계를 중심으로 - 노호래 (한국해양경찰학회보, 9(2), 2019)
본 연구의 목적은 해양경찰에도 법치주의가 실현되어야 한다는 관점에서 해양경찰법의 제정필요성과 바람직한 제정방안을 모색하는 것이다. 첫째, 해양경찰법의 필요성및 관련연구의 검토에서 해양경찰 조직체계, 해양경찰조직법 제정의 필요성, 관련연구의 검토를 하였다. 둘째로, 선진외국의 해양경찰법과 우리나라의 입법현황 분석에서US Coast Guard의 조직, 임무, 최고사령관의 임명절차와 자격을 알아보았고, 일본 해상보안청법에서의 조직, 임무, 해상보안청장관의 임명관계 및 역대 해상보안청장관의출신 등을 검토하였으며, 한국의 해양경찰조직관련 법안의 현황을 분석하고, 역대 해양경찰총수의 출신과 임명에 관하여 분석하였다. 끝으로 바람직한 제정방안을 모색하였다. 현재 해양경찰의 치안정감은 2인으로 후보군이 협소하므로 확대시켜 치안감까지 후보군으로 하는 것이 합당하고, 해양경찰 자체 청장 배출로 인한 해양경찰 사기가 진작될 수 있다는 장점이 있다. 해양경찰위원회가 단순한 자문기구로 전락할 수도있으므로 해양경찰위원회의 독자적인 사무기구가 필요하고, 해양수산부장관의 재의요구에 따라 다시 의결한 사항의 구속력에 대해 아무런 규정을 두고 있지 않다. 해양경찰위원회가 재의결한 경우의 효력에 대해서도 구체적으로 규정해야 한다. The purpose of this study is to review necessity need of maritime police act and a desirable plans acting of Maritime Police Act through realization perspective of constitutionalism in the Korea Coast Guard organization. First, the review of the need for maritime police law and related research was conducted to review the Korea Coast Guard organization system, the need for the enactment of the Maritime Police Organization Act, and related research. Second, Analysis of foreign Coast Guard Police Acts and the Present Condition Analysis of legislation in Korea is carried out. This study reviewed mission of US Coast Guard, the nominating process of supreme commander of US Coast Guard and recognized, and also mission of Japan Coast Guard, the nominating process of ministers of Japan Coast Guard and recognized. This study analyzed the current status of the bill related Korea Coast Organization and appointment of former Korea Guard chiefs. Finally, a desirable measure of legislation was sought. Currently, Two Chief Superintendent Generals have a small number of candidates, so it is fair to expand them to become candidates for the post Senior Superintendent General, and such a bill has the advantage that morale of Korea Coast guard could be boosted by the appointment of the Coast Guard's own commissioner. In other words, those with 15 years of experience in Korea Coast guard are judged to have a reasonable aspect. An independent secretariat of the Coast Guard committee is needed because the committee may be reduced to a mere advisory body. And there is no regulation on the binding power of the items that have been voted on again under the request of the Minister of Maritime Affairs and Fisheries. There is also a need to specify the effectiveness of the coast Guard committee's re-declaration. KCI Citation Count: 1